Blended Learning Model of Ulumul Hadith Through Whatsapp Media - Muhtar Tajuddin; Imam Syafi'i (Nazhruna: Jurnal Pendidikan Islam, 2021)
This study aims to develop the Ulumul Hadits learning design with the Blendel Learning model with Whatsapp media in non-formal Islamic educational institutions, namely student Islamic boarding schools. The development model used is ADDIE: analysis, design, development, implementation, and evaluation. In this research, the stages of development carried out are analysis, design, and development. The blended learning model is a combination of face-to-face learning in class (onsite) and distance learning through media (online). Onsite learning of Ulumul Hadith is carried out by lectures, presentations, and discussions. Whereas online learning can be done by providing various kinds of learning resources, namely pdf files, power point files, study video recordings, catch-up videos. Meanwhile, learning evaluation is carried out directly during face-to-face learning, quizzes, and final semester exams.